N-Hydroxyimides and hydroxypyrimidinones as inhibitors of the DNA repair complex ERCC1–XPF. Issue 19 (1st October 2015) - Chapman, Timothy M.; Wallace, Claire; Gillen, Kevin J.; Bakrania, Preeti; Khurana, Puneet; Coombs, Peter J.; Fox, Simon; Bureau, Emilie A.; Brownlees, Janet; Melton, David W.; Saxty, Barbara
Graphical abstract